D4. MCA/UtA ratio at first observation is associated with birthweight in late onset IUGR. (12th August 2016) - Simeone, Serena; Pina Rambaldi, Marianna; Serena, Caterina; Ottanelli, Serena; Mecacci, Federico
Abstract: Introduction : MCA and uterine artery Doppler PI are commonly used in the evaluation of IUGR. Targets : This retrospective pilot study aims to investigate whether MCA/UtA ratio may identify adverse outcome in late onset IUGRs. A cohort of 69 pregnancies affected with late IUGR which underwent labor induction according to local protocols was retrospectively revised on the relationship between MCA/UtA ratio at first observation and the following adverse outcomes: cesarean section for nonreassuring fetal status, birthweight (expressed as percentile and continuous values, umbilical artery pH, NICU admission and Apgar score < 7 after 1 and 5 min. Results : The study population included 75.4% nulliparous women. Mean gestational age was 36.7 and 38.7 weeks' gestation for diagnosis and induction, respectively. MCA/UtA ratio resulted significantly associated with a lower trend in birthweight, with a variation of 109.72 g for each unit considered ( p  = 0.040). The other outcomes considered showed no association. Conclusions : MCA/UtA ratio at first observation may be associated with lower birthweight in late onset IUGRs. Further prospective studies are expected.